TANGGUNG JAWAB PEMASYARAKATAN TERHADAP HAK ATAS KEBEBASAN BERIBADAH NARAPIDANA MUSLIM - Zakiy Bima (Universitas Halu Oleo, 2020)
There are local regulations regarding the rights of citizens exercise in accordance with the religious, Islam is the religion of the dominant country because of a number of most people. Everyone free people to run, no more getting ganguan or disrupt their nets worship no exception for an inmate. Are equal to Indonesian citizens. Personality spiritual guidance in the form of Islam in a correctional institution is disenchanting many prisoners, make them aware of and did not want any more repeated crimes. But was running the religious right is fairly for every Muslim prisoner, whether any prisoners have the freedom to worship, to depart from this writers with research who uses the interpretive in data obtained from the descriptive verbal, observation and in use.